Using the Positive Peers Mobile App to Improve Clinical Outcomes for Young People With HIV: Prospective Observational Cohort Comparison - Mary M Step; Jennifer McMillen Smith; Steven A Lewis; Ann K Avery (JMIR Publications, 2022)
BackgroundDisparities in HIV outcomes persist among racial, gender, and sexual minorities in the United States. Younger people face a greater risk of contracting HIV, often living without knowledge of their HIV status for long periods. The Positive Peers App (PPA) is a multifunctional HIV support tool designed to improve HIV-related clinical outcomes for young people with HIV. The app was designed according to the specifications of an in-care young adult HIV community in Northeast Ohio. Data provided in this study provide preliminary evidence of the usefulness of PPA as a relevant tool for engaging this clinical patient population in care and facilitating viral suppression. ObjectiveIn this study, we aimed to describe variations in PPA use and examine the associations between use and HIV clinical outcomes between self-selected user and nonuser cohorts in the same clinical population. MethodsThe PPA was offered free of charge to persons with HIV, aged 13 to 34 years of age, diagnosed with HIV within the last 12 months, out of care for 6 months during the last 24 months, or not virally suppressed (HIV viral load >200 copies/mL) in the prior 24 months. Baseline and 6- and 12-month surveys were administered via an audio computer-assisted self-interviewing system to all participants. The app's user activity was tracked natively by the app and stored in a secure server. Participant demographic and HIV care data were extracted from clinical records within 12 months before the start of the study and across the duration of the study period. HIV care outcomes of PPA users (n=114) were compared with those of nonusers (n=145) at the end of the study period (n=259). ResultsThe analysis showed that younger PPA users (aged 13-24 years) were more likely to obtain HIV laboratories (adjusted odds ratio 2.85, 95% CI 1.03-7.90) and achieve sustained viral suppression than nonusers (adjusted odds ratio 4.2, 95% CI 1.2-13.9). ConclusionsThe PPA appears to help younger users sustain HIV suppression. The app offers an important tool for addressing this critical population. The PPA remains in the field and is currently being adopted by other localities to facilitate their efforts to end the HIV epidemic. Although our reported observational results require additional validation and stringent ongoing surveillance, the results represent our best efforts in a pilot study to provide a measure of efficacy for the PPA. Next steps include a large-scale evaluation of the PPA acceptability and effectiveness. Given the building evidence of user reports and outcomes, the freely available PPA could be a helpful tool for achieving Ending the HIV Epidemic goals.